1984
DOI: 10.1002/anie.198403953
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding and Protein Association

Abstract: The biosynthesis of proteins leads to linear chain1 molecules with a well-defined amino acid sequence that is unambiguously determined by a corresponding polynucleotide sequence at the level of the gene. The underlying mechanism of transcription and translation is based upon the complementarity of pyrimidine and purine bases, on the one hand, and the genetic code, on the other. As indicated by denaturationhenaturation experiments, the one-dimensional structural information encoded in the polypeptide chain gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 153 publications
3
44
0
1
Order By: Relevance
“…This is supported by the coordinate dissociation, unfolding, and inactivation observed for aldolase at extremes of pH (36). Furthermore, direct evidence that quaternary structure provides stability was shown by monomeric aldolase with increased susceptibility to urea-induced inactivation compared to the same mutant tetrameric enzyme (Fig.…”
Section: Methodsmentioning
confidence: 62%
“…This is supported by the coordinate dissociation, unfolding, and inactivation observed for aldolase at extremes of pH (36). Furthermore, direct evidence that quaternary structure provides stability was shown by monomeric aldolase with increased susceptibility to urea-induced inactivation compared to the same mutant tetrameric enzyme (Fig.…”
Section: Methodsmentioning
confidence: 62%
“…6) may be a consequence of the size of the polypeptide chain. Other work (Jaenicke, 1984;Teschner et al, 1987) has shown that polypeptide chains more than about 300 amino acids in length often refold very slowly and/or inefficiently because of the failure to co-ordinate the processes of chain folding and domain pairing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the rate of re-activation of many large polypeptide chains (> 300 amino acids) is slow and often inefficient, owing to improper pairing of domains (Jaenicke, 1984;Teschner et al, 1987). The Mr of the monomeric wheat-germ enzyme is approx.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Noncovalent aggregation describes association where the partially denatured protein molecules associate inter-molecularly via hydrophobic interactions in order to minimize the unfavorable exposure of hydrophobic amino acid residues to water. 29 Covalent aggregation of proteins is actually a chemical change, which involves the formation of new bonds. Thus, although sometimes categorized as a physical degradation reaction, it would be more appropriate to categorize covalent aggregation as chemical instability (section below) rather than physical instability of the protein.…”
Section: Noncolvalent Aggregationmentioning
confidence: 99%